Digital didactic mediators in the professional formation - Elena Camilo-Parrón; José Manuel Izquierdo-Pardo; María Elena Pardo-Gómez; José Manuel Izquierdo-Lao (Maestro y Sociedad, 2018)
The objective of this work is to present the different classifications that didactic mediators have, deepen into its use advantages and highlighting the possibilities that last generation didactic mediators offer and specifically the multimedia in the professional fornation. It is exemplified with a multimedia about Suitberto Goire Castilla work, prominent plastic artist of Santiago de Cuba, with a wide plastic doing in which are included posters, CD mask, logos, drawings and paintings, which converts it in an important didactic media to enclose university students of any career to the artist labour.